2022
DOI: 10.1007/s40262-022-01135-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics and Pharmacodynamics of Fostamatinib and Its Active Moiety R406

Abstract: Fostamatinib is the first approved spleen tyrosine kinase inhibitor for chronic immune thrombocytopenia. This review summarizes the clinical development, pharmacokinetics, pharmacodynamics, drug–drug interactions, adverse events, and comprehensive analyses of fostamatinib. While integrating these findings, we discuss the fostering and improvement of fostamatinib for further clinical applications. Fostamatinib is designed as a prodrug and cleavage of its active moiety R406 in the intestine. As R406 is the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…At the same time, as indicated by the distribution patterns of plasma R406 concentrations of responders and non‐responders (Figure S4), no clear exposure‐response relationship was observed in our study. In addition, a population pharmacokinetic/pharmacodynamic analysis using data from two phase 3 studies in ITP patients showed a higher R406 concentration in responders than in non‐responders at week 12, but not between weeks 14–24 or at week 24, ruling out any relationship between R406 exposure and efficacy 27–29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, as indicated by the distribution patterns of plasma R406 concentrations of responders and non‐responders (Figure S4), no clear exposure‐response relationship was observed in our study. In addition, a population pharmacokinetic/pharmacodynamic analysis using data from two phase 3 studies in ITP patients showed a higher R406 concentration in responders than in non‐responders at week 12, but not between weeks 14–24 or at week 24, ruling out any relationship between R406 exposure and efficacy 27–29 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, a population pharmacokinetic/pharmacodynamic analysis using data from two phase 3 studies in ITP patients showed a higher R406 concentration in responders than in non-responders at week 12, but not between weeks 14-24 or at week 24, ruling out any relationship between R406 exposure and efficacy. [27][28][29] ITP patients treated with TPO-RAs experience an increased risk of thrombosis and platelet overshoot. [9][10][11] In our study, treatment with fostamatinib did not lead to platelet overshoot (>400 000/μl) or thromboembolic AEs.…”
Section: Discussionmentioning
confidence: 99%
“…Fostamatinib has been tested in various immune-mediated diseases such as RA, chronic immune thrombocytopenia, autoimmune hemolytic anemia, and IgA nephropathy [ 105 ]. It is the first SYKi approved for the treatment of chronic immune thrombocytopenia by blocking signal transduction through Fcγ receptors involved in the antibody-mediated destruction of platelets by immune cells [ 106 ].…”
Section: Spleen Tyrosine Kinase Inhibitors (Sykis)mentioning
confidence: 99%
“…Fostamatinib is initially appeared as a new means for RA treatment because it was found to have important affection in amplifying synovial inflammation, but after experiments found that Fostamatinib had a high probability of AE during treatment, and the therapeutic effect was lower than that of adalimumab, so it did not pass the regulatory application [3]. In 2009, fostamatinib was discovered to inhibit platelets of macrophages by inhibiting Syk [3]. Two parallel controlled trials FIT1 (NCT02076399) and FIT2 (NCT02076412) showed that fostamatinib had a significant effect on platelets, and it was acknowledged by the FDA after 9 years.…”
Section: Fostamatinib Synthesismentioning
confidence: 99%
“…R788 is rapidly hydrolyzed by intestinal alkaline phosphatase to R406, and R406 is absorbed by the human body. And the related products can be mainly observed in plasma [3]. According to the results of the radiotracer, R406 is distributed to the outer position of the blood vessel, and the steady-state volume of distribution is 256±92.…”
Section: Applicationmentioning
confidence: 99%